Seventeenth-century Prayer Books of Cistercian Nuns in the Collectionof the Parish Library of St Bartholomew and St Hedwig in Trzebnica - Anna Sutowicz (Wrocławski Przegląd Teologiczny)
Part of a collection held by Cistercian nuns was deposited in the Library of Trzebnica Parish. Among other works are three manuscript prayer books dated to the 17th century. Spiritual Meditations, dedicated to Katarzyna Rajska by Cistercian monk Kasper of Przemęt, is composed of several parts. Among them, the most interesting are the ponderings on the Eucharistic and a treatise about the preparation for a holy death. The work Instruction of Spiritual Exercise is unsigned, nor do we know its owner. The main body of this manuscript consists of 40 meditations focused on the reform of religious life. The last example in the collection belonged to Abbess Krystyna Pawłowska and was the gift of a Carmelite nun, Agnieszka of Jesus the Lamb. Its author, Bonawentura Frezer, a Discalced Carmelite, is a known 17th-century preacher and writer of mystical literature. His Protestations and various acts constitute a collection of mystical monologues on the presence of God. All of these manuscripts were prepared to support the personal prayers of the Trzebnica nuns and have been traced to long use. Thus, the texts form the right research material for historians of religious spirituality in the Baroque period.